What do reflective writings of clinical year students say to medical educators?; a qualitative study. - Akturan, Selçuk; Tuncel, Bilge; Güner, Yasemin; Duman Dilbaz, Ayşenur; Üçüncüoğlu, Melek; Ayazoğlu, Canan (Reflective Practice, 2023)
It is aimed to reveal the concepts and values on undergraduate medical education within the clinical students' reflective writings, and to reveal what the students' suggestions are to improve medical education in their reflective writings. This is a qualitative study, and the reflective writings of the 5th year students were examined. Qualitative document analysis method was used to evaluate and interpret the data to reveal meaning, gain understanding and develop empirical knowledge. As a result of the content analysis of 192 reflective writings obtained from the students, 8 themes were extracted. Themes covering many important concepts such as self-regulated learning, professional concerns, health literacy, problems related to professional ethical values, effective communication challenges, emotional challenges, limitations in clinical training have emerged. Subjects revealed from reflective writings give medical educators important clues about which topics should be developed in medical education. We think that analyzing reflective writings at regular intervals in the evaluation processes of integrated reflection training programs will provide important data to medical educators on development of undergraduate medical education. Therefore, students' reflective writing can be an important tool for the development of the curriculum.